2021
DOI: 10.1007/s13300-021-01116-9
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-Like Peptide 1 Receptor Agonist Usage in Type 2 Diabetes in Primary Care for the UK and Beyond: A Narrative Review

Abstract: The scientific landscape of treatments for type 2 diabetes (T2D) has changed rapidly in the last decade with newer treatments becoming available. However, a large proportion of people with T2D are not able to achieve glycaemic goals because of clinical inertia. The majority of T2D management is in primary care, where clinicians (medical, nursing and pharmacist staff) play an important role in addressing patient needs and achieving treatment goals. However, management of T2D is challenging because of the hetero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 79 publications
(141 reference statements)
0
4
0
Order By: Relevance
“…The benefits of glucose control and reduction of CV risk with GLP-1 RAs have also been proven in non-obese patients with T2D [ 16 , 21 , 37 ]. However, although the limitation by the Spanish National Health Service could affect the use of GLP-1 RAs, it may not be the major reason for the majority of patients, as other countries without the BMI limitation have similar prescription rates as Spain [ 26 , 38 , 39 ].…”
Section: Potential Reasons That Limit the Use Of Glp-1 Ras Based On T...mentioning
confidence: 99%
“…The benefits of glucose control and reduction of CV risk with GLP-1 RAs have also been proven in non-obese patients with T2D [ 16 , 21 , 37 ]. However, although the limitation by the Spanish National Health Service could affect the use of GLP-1 RAs, it may not be the major reason for the majority of patients, as other countries without the BMI limitation have similar prescription rates as Spain [ 26 , 38 , 39 ].…”
Section: Potential Reasons That Limit the Use Of Glp-1 Ras Based On T...mentioning
confidence: 99%
“…Glucagon-like peptide-1 (GLP-1) receptor agonists, exenatide, lixisenatide, liraglutide, dulaglutide and semaglutide, are among the recent subcutaneous treatment options that provide better glycemic improvement and weight loss in patients with type 2 diabetes according to the current guidelines (1,2).…”
Section: Introductionmentioning
confidence: 99%
“…Although GLP-1RA shows advantages in reducing glucose and weight ( 12 ), adverse reactions can not be ignored. Studies have shown that the most common side effects of GLP-1RA are from the gastrointestinal tract, including nausea, vomiting, diarrhea, and constipation ( 13 ).…”
Section: Introductionmentioning
confidence: 99%